"Animals Like Us": Identifying with Nonhuman Animals and Support for Nonhuman Animal Rights. (4th March 2018) - Plante, Courtney N.; Reysen, Stephen; Roberts, Sharon E.; Gerbasi, Kathleen
ABSTRACT: While anthropomorphizing nonhuman animals has been shown to increase identification with them and, by extension, concern for their wellbeing, little research has directly tested whether identifying with nonhuman animals is similarly associated with concern for their wellbeing. We tested hypotheses related to this premise across three cross-sectional studies. In study 1 ( n = 224), we tested the hypothesis that therians—a group of people who self-identify with nonhuman animals, show greater concern for nonhuman animal rights than non-therian furries—people with a fan-like interest in media featuring anthropomorphized animal characters. In study 2 ( n = 206), we further tested this hypothesis using implicit and explicit measures of identification with nonhuman animals to predict behavioral intentions to support nonhuman animal rights. In study 3 ( n = 182), we tested the generalizability of our findings in a sample of undergraduate students. Taken together, the studies show that explicit, but not implicit, identification with nonhuman animals predicts greater support for their rights. The implications of these findings for research on anthropomorphism and animal rights activism are discussed, as well as the limitations of these findings and possible avenues for future research.